Case report: a cataract induced by bleomycin in a patient with testicular cancer - Wan Zhang; Wan Zhang; Yinghua Ji; Yinghua Ji; Yufei Sun; Yufei Sun; Keya Zhi; Keya Zhi; Han Yang; Han Yang; Min Zhang; Min Zhang; et al. (Frontiers Media S.A., 2024)
BackgroundBleomycin is a glycopeptide antibiotic with outstanding anti-tumor effects. A major adverse effect of bleomycin is lung fibrosis. However, the development of cataracts as a severe adverse effect has not been reported.Case summaryHerein, we describe the first case of cataract induced by bleomycin therapy in a 22-year-old male with testicular cancer. After surgical intervention and following five successive chemotherapy cycles of the BEP regimen, including bleomycin, etoposide and cisplatin, the patient reported a gradual painless loss of vision, with substantial decline in visual ability, especially in the right eye. Following comprehensive eye examinations, a cataract was diagnosed. Eventually, the patient underwent phacoemulsification and received replacement of the intraocular lenses.ConclusionBleomycin can cause cataracts, which induces a significant loss of vision. Therefore, clinicians should observe early symptoms and properly adjust treatment to prevent aggravation of symptoms.